The heirloom - Lewis, Beverly, 1949- (Bethany House, a division of Baker Publishing Group, 2023)
"Clara Bender believes a visit to Hickory Hollow may help her find direction after her father remarries. While restoring an heirloom quilt with her great-aunt Ella Mae Zook, the two form a warm bond. When Clara's life is again upended by an unexpected incident and a young Amish man, will she find where her heart belongs?"--